Learning the Russian reflexive nouns in Lithuanian schools - Mažulis, F. (Psichologija, 1966)
The question how to learn the Russian reflexive nouns in Lithuanian school has not been examined yet. The schools have not well-established teaching traditions; the themes and their scope are being changed often. The reflexive nouns have been taught the same as in Russian schools over the period of time not paying attention to the distinction of Lithuanian schools. The students make many mistakes in using reflexive nouns.After examining the writings of 2144 students, 567 mistakes in using the reflexive nouns were observed. In spoken language the students also are making pronunciation mistakes.The reflexive nouns are being used incorrectly because of the influence of mother tongue: they are not using the Russian reflexive nouns when the corresponding Lithuanian noun is not reflexive and on the contrary. Furthermore, the students make mistakes in using the nouns which are not reflexive in Russian language and which can be both reflexive and not reflexive (accusative) in Lithuanian language, also when the reflexive nouns match only partially, only by one meaning.
Keywords: reflexive nouns; Russian language; language learning